Quality of Care and Interhospital Collaboration: A Study of Patient Transfers in Italy - Lomi, Alessandro (2014)
OBJECTIVES: We examine the dynamics of patient sharing relations within an Italian regional community of 35 hospitals serving approximately 1,300,000 people. We test whether interorganizational relations provide individual patients access to higher quality providers of care. METHODS: We reconstruct the complete temporal sequence of the 3461 consecutive interhospital patient sharing events observed between each pair of hospitals in the community during 2005-2008. We distinguish between transfers occurring between and within different medical specialties. We estimate newly derived models for relational event sequences that allow us to control for the most common forms of network-like dependencies that are known to characterize collaborative relations between hospitals. We use 45 day risk-adjusted readmission rate as a proxy for hospital quality. RESULTS: After controls (e.g., geographical distance, size, and the existence of prior collaborative relations), we find that patients flow from less to more capable hospitals. We show that this result holds for patient being shared both between as well as within medical specialties. Nonetheless there are strong and persistent other organizational and relational effects driving transfers. CONCLUSIONS: Decentralized patient sharing decisions taken by the 35 hospitals give rise to a system of collaborative interorganizational arrangements that allow patient to access hospitals delivering a higher quality of care. This result is relevant for health care policy because it suggests that collaborative relations between hospitals may produce desirable outcomes both for individual patients, as well as for regional health-care systems.